2009
DOI: 10.1038/sc.2009.105
|View full text |Cite
|
Sign up to set email alerts
|

Oral baclofen administration in persons with chronic spinal cord injury does not prevent the protective effects of spasticity on body composition and glucose homeostasis

Abstract: Study design: Correlation study. Objectives: To determine the effects of oral baclofen on body composition (fat mass (FM), fat-free mass (FFM)), extra-and intracellular fluid compartments and glucose homeostasis (plasma glucose and plasma insulin concentrations) in individuals with spinal cord injury (SCI) after controlling for spasticity. Settings: Laboratory settings at the University of Michigan, MI, USA. Methods: Fifteen individuals with chronic motor complete SCI (32 ± 8 years old, 25 ± 5 kg/m 2 , C6-T11,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…29 This led the same investigators to hypothesize that the inhibitory effects of oral baclofen on spasticity may obliterate the aforementioned effect. 46 Contrary to the hypothesis, oral baclofen administration did not attenuate the protective effects of spasticity on body composition and metabolic profile after SCI and was negatively associated with the homeostatic model assessment index. 46 The positive relationship between spasticity and muscle size as well as lean mass has recently been explained by the effect of spasticity on the circulating plasma IGF-1.…”
Section: % Of Individuals With Sci Had a Testosterone Level Gorgey mentioning
confidence: 71%
See 2 more Smart Citations
“…29 This led the same investigators to hypothesize that the inhibitory effects of oral baclofen on spasticity may obliterate the aforementioned effect. 46 Contrary to the hypothesis, oral baclofen administration did not attenuate the protective effects of spasticity on body composition and metabolic profile after SCI and was negatively associated with the homeostatic model assessment index. 46 The positive relationship between spasticity and muscle size as well as lean mass has recently been explained by the effect of spasticity on the circulating plasma IGF-1.…”
Section: % Of Individuals With Sci Had a Testosterone Level Gorgey mentioning
confidence: 71%
“…46 Contrary to the hypothesis, oral baclofen administration did not attenuate the protective effects of spasticity on body composition and metabolic profile after SCI and was negatively associated with the homeostatic model assessment index. 46 The positive relationship between spasticity and muscle size as well as lean mass has recently been explained by the effect of spasticity on the circulating plasma IGF-1. 47 Those with MAS greater than 2 have 44% higher plasma IGF-1 than those with lower MAS.…”
Section: % Of Individuals With Sci Had a Testosterone Level Gorgey mentioning
confidence: 71%
See 1 more Smart Citation
“…31 It also has been suggested that spasticity may promote a favorable body composition and muscle mass. 32 Accordingly, it may be that our findings are indicative of the inability of BMI to differentiate between fat-and fat-free mass.…”
Section: Discussionmentioning
confidence: 83%
“…Its incidence after a stroke is 17% to 38% [2,3]. Moreover, the severity of spasticity increases over time [4] and induces significant pain, contractures, joint subluxations or dislocations, peripheral neuropathy and pressure ulcers [5].…”
Section: Introductionmentioning
confidence: 99%